A comparison of weight gain between HIV exposed uninfected and HIV unexposed uninfected infants who received KMC at Chris Hani Baragwanath Academic Hospital - Leshata Abigail Mapatha; Firdose Lambey Nakwa; Mantoa Mokhachane (Frontiers Media S.A., 2022)
IntroductionKangaroo Mother Care (KMC) has been associated with improved growth in low birthweight infants and reduction in hypothermia, hypoglycaemia, apnoeas, sepsis, hospital stay, and mortality. The growth of HIV-infected children is poorer than those who are HIV-uninfected. There is paucity of data on weight gain in the HIV-exposed uninfected (HEU) infants compared to HIV-unexposed uninfected (HUU) infants receiving KMC.AimThis study compared the weight gain of HEU and infants HUU from admission to the KMC ward until 12 months corrected age (CA) follow-up visit.MethodsRetrospective record review of the neonates admitted in KMC at Chris Hani Baragwanath Hospital over a 2-year period (2012-2013). The weight gain was assessed via weight velocity using the formula; weight/kg/day from admission to KMC to discharge, and g/ week at term, 3, 6 and 9- and 12-months (CA). The demographics were collected and analyzed using Statistica.ResultsSeventy-seven (129/166) percent of the mothers were HIV negative. HIV negative mothers were younger (25.9 vs. 31.6 years; p = 0.000) and had fewer pregnancies (p = 0.02). There was no difference between the gestational age (30.3 ± 2.53 vs. 30.8 ± 2.88 weeks; p = 0.35) and birthweight (1,345 g ± 234 vs. 1,314 g ± 209; p = 0.47) between HEU and HUU. There were no differences in the weight gain (23.83 g ± 12.2 vs. 23.22 g ± 15.2; p = 0.83) in KMC. There was no differences in weight gain at the different follow-up time points between the two groups.ConclusionBoth HEU and HUU groups of infants showed reasonable weight gain despite maternal HIV status.